Nickel alloys for electronics (The Institute, 1987)
This reference book is intended to provide information that will be directly applicable to engineers and designers in evaluating and applying the nickel alloys that are most useful to the electronics industry. The materials included in this reference book are based on generic alloys that have industry specifications and Unified Numbering System (UNS) numbers. -- Provided by publisher.
Cover title.
Keywords: Electronics -- Materials.; Nickel alloys.; elektronické knihy; electronic books